Diet effects on survivorship and developmental parameters of tufted apple bud moth, Platynota idaeusalis (Walker) (Lepidoptera: Tortricidae) - Dominguez Gil, Oscar; McPheron, Bruce (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
Survival of larvae, developmental time, pupal and adult weights of the tufted apple moth Platynota idaeusalis (Walker) (Lepidoptera: Tortricidae), were monitored in the laboratory for a comparison of performance among a lima bean-based synthetic diet and four different host plant species: apple, Malus domestica (Bork.) cv. Red Yorking; black raspberry, Rubus occidentalis L.; broad-leaved plantain, Plantago major L.; and dandelion, Taraxacum officinale Wiggers. Artificial diet proved to be the best diet for P. idaeusalis in survivorship and in all the developmental parameters studied. Excluding artificial diet, survivorship was highest when feeding on apple, and lowest on dandelion at pupation, and at adult eclosion. Black raspberry and plantain were intermediate in their effects. Developmental time on apple was about the same as dandelion-fed larvae, whereas larvae feeding on plantain had the longest developmental time taken to pupation and adult eclosion among all diets. Female larvae reared on black raspberry emerged 2.6 days later than males, compared with 0.3 days for apple-reared P. idaeusalis. Larvae reared on plantain produced the heaviest pupae and adult female among host plant species. followed by apple, dandelion, and black raspberry.